Pembinaan Karakter dan Keterampilan Kewirausahaan Bagi Santri Dayah Darul Muta’alimin - Jamali; Wiriani, Erni (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Character building and entrepreneurship skills for students of Dayah Darul Muta'alimin is a coaching process that aims to shape entrepreneurial character and skills in students. The purpose of character building is to shape students into individuals who have good character such as having a sense of responsibility, discipline, confidence, honesty, and noble character. Meanwhile, fostering entrepreneurial skills aims to provide knowledge and skills in managing a business. Character development is carried out through various activities such as recitation, ta'lim, moral guidance, and other activities that can shape the character of the students. Meanwhile, fostering entrepreneurial skills is carried out through training and introduction to various types of business, how to create a business, financial management, and other matters related to the business world. Character development and entrepreneurship skills for Dayah Darul Muta'alimin students have very important benefits such as being able to form good student character, improve entrepreneurial abilities, and open job opportunities for students after graduating from Dayah. Therefore, building character and entrepreneurial skills needs to be carried out continuously so that students can have sufficient provisions to face future challenges.